A method to calculate the vertical force produced during the eggbeater kick - Oliveira, N.; Sanders, R. H. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
The eggbeater kick is a technique used in water polo and synchronised swimming. Assessing eggbeater kick performance or comparing different performers has been done by determining the height achieved during the kick in the vertical position (Sanders 1999; Homma & Homma 2006; Klauck 2006). Such methods are limited to the position of one anatomic marker (i.e. vertex, trochanter) and do not account for the subject's mass or buoyancy factors. The purpose of this study was to develop a method to determine the vertical force produced during the eggbeater kick.